Improved Clinical Outcomes with Appropriate Meropenem De-escalation in Patients with Febrile Neutropenia - Tyler Luu; Austin Fan; Reid Shaw; Hina Dalal; Jenna Adams; Maressa Santarossa; Gail Reid; Stephanie Tsai; Nina M. Clark; Fritzie S. Albarillo (Journal of Global Infectious Diseases)
Introduction: Antibiotic stewardship is a critical aspect of managing cancer patients with febrile neutropenia (FN) to limit the development of drug-resistant organisms and minimize adverse drug effects. Thus, it has been recommended that patients with FN receiving empiric antibiotics should be re-evaluated for safe antibiotic de-escalation. Methods: Subjects treated with meropenem for febrile neutropenia who met Loyola University Medical Center’s (LUMC) criteria for de-escalation were stratified based on whether meropenem was de-escalated, and 30-day all-cause mortality for both groups was assessed. Results: 181 patients met criteria for meropenem de-escalation. Sixty patients (31.3%) were ade-escalated (MDE), and 121 subjects were not (NDE). The 30-day all-cause mortality was 8.3% (n = 5/60 subjects) in the MDE group and 2.4% (n = 3/121) in the NDE group but was not statistically significant (P=0.1). Median hospital length of stay was 13 days in the MDE group versus 20 days in the NDE group (P = 0.049). CDI rate was also lower in the de-escalated group. In addition, consultations by infectious diseases physicians were more common in the de-escalation group. Logistic regression model demonstrated positive culture (OR 4.78, P = 0.03), including positive blood culture (OR 8.05, P = 0.003), and GVHD (OR 19.44, P = 0.029), and were associated with high rates of appropriate de-escalation. Immunosuppression (OR 0.22, P = 0.004) was associated with lower rates of appropriate de-escalation. Conclusion: Appropriate meropenem de-escalation in FN patients is safe and can result in improved clinical outcomes.